1986
DOI: 10.1002/tea.3660230903
|View full text |Cite
|
Sign up to set email alerts
|

A study of the latent effects of family learning courses in science

Abstract: It is well documented that students' exposure to science in the middle school is critical for their later selection of science courses, yet instruction time and course offerings in science during the middle school years are often limited. Out‐of‐School Science Experiences with funds from the National Science Foundation (DISE No. 07872) produced five short science courses intended for children in middle school grades (6, 7, and 8) and their parents that supplement normal science instruction based on topics that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Although the context for this family learning is different from a casual visit, both parents and children made significant gains in learning as measured by subject matter tests. A followup study indicated that this learning did persist and that, in particular, the classes had resulted in a long-term change in family learning behavior and family attitude toward learning (Gennaro et al, 1986).…”
Section: Informal Science Settings 63mentioning
confidence: 99%
“…Although the context for this family learning is different from a casual visit, both parents and children made significant gains in learning as measured by subject matter tests. A followup study indicated that this learning did persist and that, in particular, the classes had resulted in a long-term change in family learning behavior and family attitude toward learning (Gennaro et al, 1986).…”
Section: Informal Science Settings 63mentioning
confidence: 99%
“…Leichter, 1974Leichter, , 1978Fey, 1977;Katz, 1978). We can also find several reports which indicate positive effects of leaming with family members on science learning (Gennaro et al, 1980;Ostlund et al, 1985;Gennaro et al, 1986). The framework of &dquo;family as an educational setting for STS&dquo; holds promise.…”
Section: The Family As An Educational Setting For Stsmentioning
confidence: 66%
“…Two-thirds of the children in the telephone interview also stated that communication had increased as a result of the course. Gennaro, Hereid and Ostlund (1986) concluded that family learning courses in science were both enjoyable and challenging learning experiences. Both parents and students overwhelmingly stressed that they enjoyed the cooperative aspect of working together.…”
Section: Zoo Coursesmentioning
confidence: 97%